Recent advances and application value of circRNA in neuroblastoma - Wu, Ke; Tan, Juan; Yang, Chao (Frontiers in Oncology, 2023)
Neuroblastoma (NB) is children’s most prevalent solid malignant tumor, accounting for 15% of childhood cancer mortality. Non-coding RNA is important in NB pathogenesis. As a newly identified non-coding RNA, abnormal regulation (abnormal up-regulation or down-regulation) of the circRNAs expression is implicated in the tumorigenesis of various tumors, including NB. CircRNAs primarily regulate the expression of microRNA (miRNA) target genes by microRNA (miRNA) sponge adsorption. Clinical evidence suggests that the expression of certain circRNAs is associated with the prognosis and clinical features of NB and hence may be exploited as a biomarker or therapeutic target. This review examines circRNAs that have been demonstrated to play a function in NB.